2010
DOI: 10.1161/circulationaha.110.957332
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor-B Acts as a Coronary Growth Factor in Transgenic Rats Without Inducing Angiogenesis, Vascular Leak, or Inflammation

Abstract: Background— Vascular endothelial growth factor-B (VEGF-B) binds to VEGF receptor-1 and neuropilin-1 and is abundantly expressed in the heart, skeletal muscle, and brown fat. The biological function of VEGF-B is incompletely understood. Methods and Results— Unlike placenta growth factor, which binds to the same receptors, adeno-associated viral delivery of VEGF-B to mouse skeletal or heart muscle induced very little angiogenesis, vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 33 publications
6
113
2
1
Order By: Relevance
“…Mechanistically, VEGF-B increased phosphorylation of ERK1/2, a downstream mediator of VEGF receptor signaling in the heart, and ribosomal protein S6, indicating activation of the mTORC1 pathway. The effect of VEGF-B is consistent with our previous studies, in which VEGF-B induced mild cardiac and cardiomyocyte hypertrophy that was not converted to cardiomyopathy even upon prolonged VEGF-B overexpression (10,11). This may be because VEGF-B-induced cardiomyocyte hypertrophy is based on enhanced signaling by endogenous VEGF via endothelial VEGFR2, leading to a concomitant increase of the coronary vasculature (11).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Mechanistically, VEGF-B increased phosphorylation of ERK1/2, a downstream mediator of VEGF receptor signaling in the heart, and ribosomal protein S6, indicating activation of the mTORC1 pathway. The effect of VEGF-B is consistent with our previous studies, in which VEGF-B induced mild cardiac and cardiomyocyte hypertrophy that was not converted to cardiomyopathy even upon prolonged VEGF-B overexpression (10,11). This may be because VEGF-B-induced cardiomyocyte hypertrophy is based on enhanced signaling by endogenous VEGF via endothelial VEGFR2, leading to a concomitant increase of the coronary vasculature (11).…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, although VEGF-B inhibited DOX-induced whole-body wasting in all experiments, it did not increase body weight in healthy mice without cachexia, as we have reported previously (10,11). Mechanistically, VEGF-B increased phosphorylation of ERK1/2, a downstream mediator of VEGF receptor signaling in the heart, and ribosomal protein S6, indicating activation of the mTORC1 pathway.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We have reported that this right ventricle (RV) capillary rarefaction is associated with a decreased myocardial expression of VEGF-A. 35 Now we show that the expression of the VEGF-B splice variant [36][37][38] is likewise decreased in the tissues of failing rat RVs, further supporting the hypothesis that loss of expression of angiogenesis factors can explain the capillary rarefaction 35,39 in failing RVs. 34 …”
Section: Introductionsupporting
confidence: 60%